Evaluation of Surgical Intervention in Acute Spinal Cord Injured Patients – A review - Ramani, PS (Indian Journal of Neurotrauma, 2004)
Spinal Cord Injury is a devastating form of Neurotrauma known to mankind since antiquity. It strikes mostly the young, and leads to lifelong disability. The pathology, besides the mechanical disruption of neural tissue, involves complex biological events which are gradually unfolding and being recognised clinically and in the laboratory. Surgical stabilisation is important for early rehabilitation. The role of methyleprednisolone in acute spinal cord injury is still not convincing.
Keywords: methyleprednisolone; spinal cord injury